Historical apple cultivars that display high level of resistance to fire blight - Kása, K.; G. Tóth, M.; Hevesi, M. (International Journal of Horticultural Science, 2004)
Following the first outbreak of fire blight caused by the bacterium Erwinia amylovora (Burrill) Winslow et al. in Hungary, we have started research with the aim to screen domestic gene sources, mostly historical Hungarian apple cultivars, for disease resistance as part of an apple breeding program for multiple resistance. The present study was conducted with the aim to choose the most tolerant historical apple cultivars among 25 selected cultivars by screening their behavior towards fire blight under controlled conditions. Six cultivars were shown to be the most disease tolerant: `Batul', 'London pepin', Nemes Sóvári Alma', `Sikulai', `Szemes alma', Wilmos renet'. We evaluated these cultivars by investigating both morphological- characteristics under original environmental circumstances and fruit quality. The cultivars had a remarkable degree of fire blight resistance compared to the control cultivars. These were not competitive with the commercially grown 'Jonathan M40' during cultivar tests but on the basis of certain characteristics they could serve as genetic sources for breeding new varieties.